Improved Key Frame Extraction using Discrete Wavelet Transform with Modified Threshold Factor - Hussein Ali Aldelfy; Mahmood Hamza Al-Mufraji; Thamir R. Saeed (Universitas Ahmad Dahlan, 2018)
Video summarization used for a different application like video object recognition and classification. In video processing, numerous frames containing similar information, this leads to time consumption and slow processing speed and complexity. By using key frames reducing the amount of memory needed for video data processing and complexity greatly. In this paper key frame extraction of Arabic isolated word using discrete wavelet transform (DWT) with modified threshold factor is proposed with different bases. The results for different wavelet basis db, sym and coif show the best result for numbers of key frames at the threshold factor value (0.75).